Relevansi Profil Pancasila Kurikulum Merdeka Dengan Evaluasi Nilai Karakter Nabi Muhammad Dalam Syair Burdah - Mihrab Afnanda; Nuril Huda; Dina Hermina (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
The research describes the relevance of independent curriculum learning with the evaluation of the character values of the Prophet Muhammad in Syair Burdah. This research uses descriptive qualitative method with data source Syair Burdah. Based on the results: (1) stanza 29 that the Apostle has the character value of Diligence, and the relevance of the independent curriculum also emphasizes that students must be diligent and focused in learning; (2) stanzas 30, 31 and 32 that the Apostle has the character value of restraining lust and zuhud and the relevance of the independent curriculum emphasizes students' self-control; (3) stanzas 34 and 40 that the Apostle has the character value of a wise and wise leader and the relevance of the independent curriculum emphasizes wise and responsible students; (4) stanza 35 that the Apostle has the character value of honesty (siddiq) and the relevance of the independent curriculum emphasizes students to be honest in everything; (5) stanza 39 contains that the Apostle has the character value of courtesy and the relevance of the independent curriculum emphasizes students to be polite.